Clinical Features, Risk Factors, and Outcomes of Acute Coronary Syndrome in Young Sudanese Patients: A Retrospective Single-Tertiary Care Center Study - Osman Elsayd Osman; Reem Mohamed Osman; Atka Ahmed Abd Elkariem; Sahar Alfadil; Rawan Mohamedosman; Imad Fadl Elmula (Sudan Journal of Medical Sciences, 2025)
Background: Coronary artery disease (CAD) is a leading cause of death worldwide, even in young patients. This study aimed to characterize the clinical features, risk factors, and prognosis of acute coronary syndrome (ACS) in young Sudanese patients.